IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN KARAWITAN DI SEKOLAH DASAR NEGERI BANGUNHARJO KECAMATAN SEWON KABUPATEN BANTUL - Naim Kurniatin; F.X Sindhuredja (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: This study aims to find the implementation of character education students in learning musical in SD N Bangunharjo Sewon Bantul. This study a qualitative research study used to examine the condition of natural objects. The subjects of this study consisted of one principal, one teacher musicians, two classroom teachers and six student representatives I AB, IIAB and III AB. Research data collection techniques is done by observation, interview and documentation. The data obtained are tested its validity by increasing persistence and triangulation. Data analysis techniques to interview is with data reduction, data presentation and conclusion. The results showed that in SD N Bangunharjo Sewon Bantul has sought integrated implementation of character education in musical learning by way of informing students when in SD N Bangunharjo No musical learning in which form the character of the child, the child habituation to the musical arts, animating or more children give priority to the wishes of students, make learning karawitan be fun and not boring as an example once a month are invited to see performances in the ISI and included musical competitions, motivate students about Indonesian culture. Instill character in a way trained through a variety of musical learning as an example of the cohesiveness play musical rhythm of the music, polite, responsible for the musical instruments being played, discipline in part-bain instrument. Of musical learning are taught the values of the characters that appear are manners, religious, patriotism, curiosity, communicative, sense of nationality, discipline, honesty, responsibility, independence and tolerance, trying to establish the values of other characters. However, in implementing the character education has factors supporting and inhibiting factors are already available supporting factors specific musical teacher, has been the availability of rooms musical, student interest and involvement of all teachers while inhibiting factors are still many students who love to interfere with his friend, student street fro, less learning time, the tool is simple and less complete musical instruments as well as students are more pleased with today's technology.Â